2018
DOI: 10.1117/1.jbo.23.4.048001
|View full text |Cite
|
Sign up to set email alerts
|

Breast tumor hemodynamic response during a breath-hold as a biomarker to predict chemotherapeutic efficacy: preclinical study

Abstract: Continuous wave diffuse optical tomographic/spectroscopic system does not provide absolute concentrations of chromophores in tissue and monitor only the changes of chromophore concentration. Therefore, it requires a perturbation of physiological signals, such as blood flow and oxygenation. In that sense, a few groups reported that monitoring a relative hemodynamic change during a breast tissue compression or a breath-hold to a patient can provide good contrast between tumor and nontumor. However, no longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In this study, the average SpO 2 changed from 98.6% to 94.4% as the supplied gas was changed from 50% O 2 gas balanced by N 2 gas to 16% O 2 gas balanced by N 2 gas. While the drop of SpO 2 in this study was smaller (98.6% → 94.4%: 4.2% difference) than the one of the previous study (97% → 91%: 6% difference) [ 28 ], the drop of SpO 2 , which is observed in a human study during breath-holding [ 63 ], guarantees that the protocol used in this study can mimic breath-holding as well. At the same time, 94.4% SpO 2 can assure the safety of the animal because this value is higher than the one (92% SpO 2 ) of people living in Aspen, Colorado where people do not have any critical health issues [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In this study, the average SpO 2 changed from 98.6% to 94.4% as the supplied gas was changed from 50% O 2 gas balanced by N 2 gas to 16% O 2 gas balanced by N 2 gas. While the drop of SpO 2 in this study was smaller (98.6% → 94.4%: 4.2% difference) than the one of the previous study (97% → 91%: 6% difference) [ 28 ], the drop of SpO 2 , which is observed in a human study during breath-holding [ 63 ], guarantees that the protocol used in this study can mimic breath-holding as well. At the same time, 94.4% SpO 2 can assure the safety of the animal because this value is higher than the one (92% SpO 2 ) of people living in Aspen, Colorado where people do not have any critical health issues [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
“…Since animals cannot perform breath-holding spontaneously, the hypoxic respiratory challenge was used to mimic breath-holding even though hypoxic respiratory challenge may not be able to mimic breath-holding perfectly. The experimental protocol used in the work (50% O 2 gas balanced by N 2 gas for 10 min → 16% O 2 gas balanced by N 2 gas for 5 min as hypoxic gas challenge → 50% O 2 gas balanced by N 2 gas for 15 min) was based on a protocol used in a previous breast cancer study by S. Lee and J. G. Kim (100% O 2 gas for 3 min → 21% O 2 gas balanced by N 2 gas for 10 min as the hypoxic gas challenge) with a minute modification [ 28 ]. In the previous study, the average pulmonary oxygen saturation (SpO 2 ) of rats changed from 97% to 91% as the supplied gas was changed from 100% O 2 gas to 21% O 2 gas balanced by N 2 gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 A preclinical study of a rat breast cancer model yielded results consistent with these findings, demonstrating that changes in during simulated breath holds could differentiate treatment and control groups and that optical changes preceded tumor volume changes. 50 Another clinical study demonstrated that compression-induced hemodynamics were able to differentiate responders from nonresponders within the first month of chemotherapy. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Many optical imaging methods for diagnosis and treatment monitoring have been reported [10][11][12][13], and we have established a two-dimensional optical imaging system with time-resolved spectroscopy (TRS) for breast cancer surveillance, as previously reported [14]. TRS is a technique that measures the time of flight, in addition to the light intensity, at the boundary of a medium.…”
Section: Introductionmentioning
confidence: 98%